The Application of Global Education in Child-Friendly School: Descriptive Study in Primary School in Sumedang - Handayani, Hany; Rahayu, Pupung; Agusfianudin, Agusfianudin (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2019)
Integration of global education in schools is considered insignificant by teachers, whereas in the face of the era of globalization, education is very important given to elementary school students, so with this consideration this research is carried out. The method used in this study is a descriptive method of the International Green School Primary School in Sumedang which implements child-friendly schooleducation. This study aims to find out how schools apply global education to subjects in the classroom. The technique of data collection is done through semi- structured interviews, observation and documentation. This study was analyzed using a grounding approach. The findings of this study highlight the implementationof global education in child-friendly schools at the Green School Elementary School.Based on these findings, Elementary School teachers found learning patterns in the implementation of global education in Primary Schools. The results obtained are: 1) increasing student understanding of international and intercultural issues and, 2) increasing student understanding of strategies to participate locally, nationally, and internationally.